Sistem monitoring dan peringatan dini banjir berbasis Internet of Things (IoT) - Ratmini, Yuli; Purwanto, Eko; Atina, Vihi (Jurnal Ilmiah Teknologi Informasi Asia, 2025)
Flood disasters are a recurring problem in Sragen Regency, primarily caused by the overflow of the Bengawan Solo River during the rainy season with high rainfall intensity and duration exceeding 4 hours. According to data from the Sragen Regency Disaster Management Agency (BPBD), over the past seven years, 46 floods have occurred in 16 villages across 20 sub-districts in Sragen Regency. The impacts of these disasters include infrastructure damage, material losses, and threats to human safety, further aggravated by the limited availability of early warning tools. To mitigate these impacts, an effective monitoring and early warning system is needed. The objective of this research is to develop an Internet of Things (IoT)-based system capable of monitoring water conditions and providing early warnings through Telegram notifications using the Blynk application. This system is designed to provide accurate and timely information regarding water levels and early flood warnings to the community in Sragen Regency. In its development, the system utilizes an HC-SR04 ultrasonic sensor to measure water surface height, an ESP32 microcontroller for data processing, and Blynk IoT and a Telegram bot as remote notification media. Additionally, visual indicators such as LED lights and a buzzer are used to provide local early warning signals regarding potential floods. The innovation offered by this IoT-based flood monitoring system focuses on real-time detection and anticipation of flood threats. This research also developed a system integrating Blynk with Telegram, enabling rapid notification delivery. Test results show that the system is capable of detecting water levels with an accuracy reaching 95%, providing early notifications with an average latency of 1.2 seconds, and maintaining connection stability up to 99%. Through this research, it is hoped to provide a significant contribution to the development of IoT-based disaster mitigation technology. Compared to conventional systems, this innovation offers high accuracy, more affordable costs, and ease of use, which is expected to assist disaster management officials and the community in mitigating flood risks and enhancing disaster preparedness in Sragen Regency.